Case Report of a Satin Guinea Pig with Fibrous Osteodystrophy That Resembles Human Pseudohypoparathyroidism - Miguel Gallego (Case Reports in Veterinary Medicine)
A case report of a 2-year-old female satin guinea pig with a history of dental overgrowth and lameness and radiological lesions of fibrous osteodystrophy is presented. The most relevant clinical findings were bone demineralization, high level of parathyroid hormone (PTH), normophosphatemia, normal ionized calcium, and low total thyroxine (tT4) with a normal renal function. Long-term treatment was based on teeth coronal reduction and maintaining a balanced diet. PTH measurement was performed with a kit suitable for rats to test 4 different paired samples of guinea pigs and resulted in similar results for each pair of measurements. Two kits routinely employed in dogs and cats failed in measuring PTH in guinea pig serum samples. The ionized calcium, PTH, and tT4 values, not previously reported in similar cases, were obtained. The determination of tT4 could be useful in the diagnosis of fibrous osteodystrophy in guinea pigs. The observed findings show similarity with human pseudohypoparathyroidism type Ia, a disease caused by an inactivating heterozygous mutation of the stimulatory G protein α subunit from the maternal genome that induces multiple hormone resistance and that courses with a syndrome called Albright hereditary osteodystrophy. Naturally occurring pseudohypoparathyroidism in animals has been reported previously only in a ferret.